1997
DOI: 10.1007/s002689900215
|View full text |Cite
|
Sign up to set email alerts
|

Recurrence after resection for ductal adenocarcinoma of the pancreas

Abstract: We analyzed the pattern of failure and clinicopathologic factors influencing the disease-free survival of 78 patients who died after macroscopic curative resection for pancreatic cancer. Local recurrence was a component of failure in 56 patients (71.8%) and hepatic recurrence in 48 (61.5%), both accounting for 97% of the total recurrence rate. About 95% of recurrences occurred by 24 months after operation. Median disease-free survival time was 8 months, and cumulative 1-, 3-, and 5-year actuarial disease-free … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

7
267
2
2

Year Published

1999
1999
2018
2018

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 400 publications
(286 citation statements)
references
References 36 publications
7
267
2
2
Order By: Relevance
“…This means that tissue injury accompanying surgical treatment may offer the specific environment which influences dissemination of cancer cells, if residual cancer cells are present in the resected margin or in the wound fluid. In pancreatic cancer treatment, disseminative cancer spreading and metastasis often follows surgical removal of the primary tumour (Sperti et al, 1997). We found that high levels of HGF exist in peritoneal fluid after pancreatic cancer surgery and that incubation with ascitic fluid strongly stimulates invasion of pancreatic cancer cells, yet this invasion was almost completely inhibited by an HGF-antagonist and neutralizing HGF antibody.…”
Section: Discussionmentioning
confidence: 94%
“…This means that tissue injury accompanying surgical treatment may offer the specific environment which influences dissemination of cancer cells, if residual cancer cells are present in the resected margin or in the wound fluid. In pancreatic cancer treatment, disseminative cancer spreading and metastasis often follows surgical removal of the primary tumour (Sperti et al, 1997). We found that high levels of HGF exist in peritoneal fluid after pancreatic cancer surgery and that incubation with ascitic fluid strongly stimulates invasion of pancreatic cancer cells, yet this invasion was almost completely inhibited by an HGF-antagonist and neutralizing HGF antibody.…”
Section: Discussionmentioning
confidence: 94%
“…Rates of curative resection remain low and adjuvant therapy failure, even after curative resection, has only limited impact2, 3, 4, 5, 6. Neoadjuvant therapy has been advocated in an attempt to increase radical resections, decrease distant recurrence and improve selection of patients for surgery.…”
Section: Introductionmentioning
confidence: 99%
“…Most patients with PDAC do not develop symptoms, such as jaundice or pain, until the tumour is already in a locally advanced or metastatic stage. Unfortunately, no curative treatment options are available for these patients, and even patients with localised disease where a curative resection is attempted frequently relapse, with mean survival ranging between 8 and 14 months (Conlon et al, 1996;Sperti et al, 1997;Trede et al, 2001). Recent advances in adjuvant therapy have achieved survival rates of 20 months , which represents an improvement, though on a low level.…”
Section: Introductionmentioning
confidence: 99%